The analysis of teachers' wait time in the English classroom at SMA 10 Padang - Salsabillah, Aini; Zainil, Yetti (Universitas Negeri Padang, 2025)
This study explores teachers’ wait time and its impact on students’ speaking participation in English classrooms at SMA Negeri 10 Padang. Speaking is one of the most challenging skills for EFL learners, as many students feel anxious, afraid of making mistakes, and lack confidence to speak. One factor that influences this situation is the teacher’s wait time, the pause given after asking a question before expecting an answer. This research focuses on two types of wait time: Wait Time 1, which occurs after the teacher’s question and before the student’s response, and Wait Time 2, which occurs after the student’s answer and before the teacher’s next move. A mixed-method design was used, combining classroom observations and stimulated recall interviews with two English teachers. The results showed that most teachers gave short pauses, ranging from one to five seconds. Longer pauses encouraged more meaningful and confident student responses, while shorter ones limited participation. The findings suggest that teachers should be more aware of their wait time to promote reflective and communicative classroom interaction.